MERENCANAKAN KEGIATAN PEMBELAJARAN (MENYATAKAN TUJUAN PEMBELAJARAN ) - Nurul Mutmainnah; Rezky Awalia Amanda; Bahri Bahri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. One step in the learning process that is always meant to yield the best results is the lesson plan. Teachers who constantly plan their lessons ahead of time are one of the keys to success. Finding out how to organize learning activities that align with specified learning objectives is the aim of this study. This study's methodology is library research, which gathers data by looking for sources and building from a variety of sources, including books, journals, and previous studies. According to the study's findings, we need to create a learning plan that we will follow in order to meet the learning objectives. Thus, in addition to being a legal document, a learning plan is a crucial tool for guaranteeing the efficiency.